Report on business attachment with Singapore Institute of Purchasing and Materials Management. - Tham, Kuo Chau. (2009)
The report provides an insight into the business attachment program with the Singapore Institute of Purchasing and Materials Management. It attempts to highlight the usefulness of the business attachment program in exposing undergraduates of the marketing specialization to the practical aspects of business attachment.